2011
DOI: 10.1016/j.applthermaleng.2010.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Solid conduction effects and design criteria in moving bed heat exchangers

Abstract: a b s t r a c tThis work presents a theoretical study of the energetic performance of a moving bed heat exchanger (MBHE), which consists of a flow of solid particles moving down that recovers heat from a gas flow percolating the solids in cross flow. In order to define the solid conduction effects, two solutions for the MBHE energy equations have been studied: an analytical solution considering only convection heat transfer (and neglecting solid conduction) and a numerical solution with the solid conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…To rationally simplify the energy conversion functions of the system, some assumptions are followed: Steady‐state process. Plug flow is assumed for solids flow and SCO 2 flow which translates into that a constant voidage is applied to the moving packed bed and the velocity of both flows are uniform in the channels. Such flow pattern is a common simplification in MPBE models Particles and interstitial air are in local thermal equilibrium and can be treated as a single continuum.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…To rationally simplify the energy conversion functions of the system, some assumptions are followed: Steady‐state process. Plug flow is assumed for solids flow and SCO 2 flow which translates into that a constant voidage is applied to the moving packed bed and the velocity of both flows are uniform in the channels. Such flow pattern is a common simplification in MPBE models Particles and interstitial air are in local thermal equilibrium and can be treated as a single continuum.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Two control strategies, feed forward control and feedback control, were presented to maintain a stable SCO 2 outlet conditions. In order to investigate the solid conduction effect in a cross flow moving bed heat exchanger, a combination of analytical solution with numerical simulation has been put forward . Results suggested that particle solids with low conductivity should be recommended to ensure a considerable heat exchanger efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…An active mobile heat exchanger (MBHE) was theoretically studied by this researcher, and the numerical outcomes demonstrate that high efficiency is harmed by solid conductivity of heat exchangers with temperature differences inside of the solid particle flow downward and recover heat from the gas flow with filtering of solids in the tangential flow [6]. A two-dimensional model is used to calculate the packed bed's effective heat transfer coefficients at temperatures ranging from 800 to 1100 degrees Celsius under constant circumstances, and the results show that the calculated effective coefficients are in agreement with those obtained in an experimental study conducted in a solar tube reactor heated by an electric furnace for manganese iron oxide particles [7].…”
Section: Introductionmentioning
confidence: 99%
“…Também, o uso de modelos auxilia a compreensão e análise de processos numa base racional. No caso da transferência de calor de leito móvel na ausência de reações químicas, a influência da condutividade térmica dos sólidos surge através do número de Biot (Bi), seja na seleção de modelos (Bertoli et al, 2017) ou na análise de desempenho térmico (Almendros-Ibanez et al, 2011). Em processos envolvendo reações químicas e um sólido transportador de energia térmica, a análise torna-se mais complicada, pois o efeito das propriedades térmicas do TE podem influenciar os rendimentos do processo.…”
Section: Introductionunclassified